DIPANGGIL KEPADA KEKUDUSAN - Agustinus Supriyadi (Bahasa Indonesia, 2020)
Humans be created in the image of God. All people are called to holiness, that is to perfection, just as the Father in heaven is perfect. The theme called to holiness is first placed in the frame of the Basic Diocese of Surabaya which deals with the great theme of the Disciples of Christ. The theme of holiness contains elements about: what, when, where, who, why and how. The Kipling method or the 5W-1H method helps the writer in describing this holiness theme. Being called to holiness in context has the same meaning as being called to be holy. Holiness itself has a charge as perfect love. Holiness and love are two inseparable things, because God is both Holy and Love. Human union with God is the essence of holiness. Holiness has a relationship with the perfection of love, so holiness cannot be understood separately from one's attitude and actions towards God through his actions towards the poor who suffer. Holiness is a lifestyle that is connected with daily life according to the Beatitues that Jesus conveyed to His disciples.